Effects of reduced-impact logging on fish assemblages in central Amazonia - Dias, Murilo S (Conservation biology : the journal of the Society for Conservation Biology, 2010)
In Amazonia reduced-impact logging, which is meant to reduce environmental disturbance by controlling stem-fall directions and minimizing construction of access roads, has been applied to large areas containing thousands of streams. We investigated the effects of reduced-impact logging on environmental variables and the composition of fish in forest streams in a commercial logging concession in central Amazonia, Amazonas State, Brazil. To evaluate short-term effects, we sampled 11 streams before and after logging in one harvest area. We evaluated medium-term effects by comparing streams in 11 harvest areas logged 1-8 years before the study with control streams in adjacent areas. Each sampling unit was a 50-m stream section. The tetras Pyrrhulina brevis and Hemigrammus cf. pretoensis had higher abundances in plots logged > or =3 years before compared with plots logged <3 years before. The South American darter (Microcharacidium eleotrioides) was less abundant in logged plots than in control plots. In the short term, the overall fish composition did not differ two months before and immediately after reduced-impact logging. Temperature and pH varied before and after logging, but those differences were compatible with normal seasonal variation. In the medium term, temperature and cover of logs were lower in logged plots. Differences in ordination scores on the basis of relative fish abundance between streams in control and logged areas changed with time since logging, mainly because some common species increased in abundance after logging. There was no evidence of species loss from the logging concession, but differences in log cover and ordination scores derived from relative abundance of fish species persisted even after 8 years. For Amazonian streams, reduced-impact logging appears to be a viable alternative to clear-cut practices, which severely affect aquatic communities. Nevertheless, detailed studies are necessary to evaluated subtle long-term effects